Regional disparities in infant mortality in Canada: a reversal of egalitarian trends - Dzakpasu Susie; Huang Ling; Joseph K S; McCourt Catherine (BMC, 2009)
Abstract Background Although national health insurance plans and social programs introduced in the 1960s led to reductions in regional disparities in infant mortality in Canada, it is unclear if such patterns prevailed in the 1990s when the health care and related systems were under fiscal duress. This study examined regional patterns of change in infant mortality in Canada in recent decades. Methods We analysed regional changes in crude infant mortality rates and in infant mortality rates among live births with a birth weight ≥ 500 g and ≥ 1,000 g in Canada from 1945 to 2002. Associations between baseline infant mortality rates in the provinces and territories (e.g., in 1985-89) and the change observed in infant mortality rates over the subsequent period (e.g., between 1985-89 and 1995-99) were assessed using Spearman's rank correlation coefficient. Trends in regional disparities were also assessed by calculating period-specific rate ratios between provinces/territories with the highest versus the lowest infant mortality. Results Provincial/territorial infant mortality rates in 1945-49 were not correlated with changes in infant mortality over the next 10 years (rho = 0.01, P = 0.99). However, there was a strong negative correlation between infant mortality rates in 1965-69 and the subsequent decline in infant mortality (rho = - 0.85, P = 0.002). Provinces/territories with higher infant mortality rates in 1965-69 (Northwest Territories 64.7 vs British Columbia 20.7 per 1,000 live births) experienced relatively larger reductions in infant mortality between 1965-69 and 1975-79 (53.7% decline in the Northwest Territories vs a 36.6% decline in British Columbia). This pattern was reversed in the more recent decades. Provinces/territories with higher infant mortality rates ≥ 500 g in 1985-89 experience relatively smaller reductions in infant mortality between 1985-89 and 2000-02 (rho = 0.82, P = 0.004). The infant mortality ≥ 500 g rate ratio (contrasting the province/territory with the highest versus lowest infant mortality) was 3.2 in 1965-69, 2.4 in 1975-79, 2.2 in 1985-89, 3.1 in 1995-99 and 4.1 in 2000-02. Conclusion Fiscal constraints in the 1990s led to a reversal of provincial/territorial patterns of change in infant mortality in Canada and to an increase in regional health disparities.